The Mental Health of Refugee Children in Canada - Hyman, Ilene; Beiser, Morton; Vu, Nhi (Refuge: Canada’s Journal on Refugees, 1996)
This paper reviews the literature on sources of stress, and the personal and social resources refugee youth use to cope with adversity. Preliminary findings from the Clarke Institute/University of Toronto Department of Psychiatry Southeast Asian (SEA) Refugee Youth Project, a study of the mental health and adaptation of SEA youth to Canada, are used to supplement findings from the literature. The review highlights research needs as well as possibilities for programs that could help promote the successful adaptation of refugee youth in Canada.